Electrocochleography-Based Tonotopic Map: II. Frequency-to-Place Mismatch Impacts Speech-Perception Outcomes in Cochlear Implant Recipients - Walia, Amit; Shew, Matthew A; Varghese, Jordan; Lefler, Shannon M; Bhat, Amrita; Ortmann, Amanda J; Herzog, Jacques A; Buchman, Craig A (Ear and hearing, 2024)
Modern cochlear implants (CIs) use varying-length electrode arrays inserted at varying insertion angles within variably sized cochleae. Thus, there exists an opportunity to enhance CI performance, particularly in postlinguistic adults, by optimizing the frequency-to-place allocation for electrical stimulation, thereby minimizing the need for central adaptation and plasticity. There has been interest in applying Greenwood or Stakhovskaya et al. function (describing the tonotopic map) to postoperative imaging of electrodes to improve frequency allocation and place coding. Acoustically-evoked electrocochleography (ECochG) allows for electrophysiologic best-frequency (BF) determination of CI electrodes and the potential for creating a personalized frequency allocation function. The objective of this study was to investigate the correlation between early speech-perception performance and frequency-to-place mismatch. This retrospective study included 50 patients who received a slim perimodiolar electrode array. Following electrode insertion, five acoustic pure-tone stimuli ranging from 0.25 to 2 kHz were presented, and electrophysiological measurements were collected across all 22 electrode contacts. Cochlear microphonic tuning curves were subsequently generated for each stimulus frequency to ascertain the BF electrode or the location corresponding to the maximum response amplitude. Subsequently, we calculated the difference between the stimulus frequency and the patient's CI map's actual frequency allocation at each BF electrode, reflecting the frequency-to-place mismatch. BF electrocochleography-total response (BF-ECochG-TR), a measure of cochlear health, was also evaluated for each subject to control for the known impact of this measure on performance. Our findings showed a moderate correlation ( r = 0.51; 95% confidence interval: 0.23 to 0.76) between the cumulative frequency-to-place mismatch, as determined using the ECochG-derived BF map (utilizing 500, 1000, and 2000 Hz), and 3-month performance on consonant-nucleus-consonant words (N = 38). Larger positive mismatches, shifted basal from the BF map, led to enhanced speech perception. Incorporating BF-ECochG-TR, total mismatch, and their interaction in a multivariate model explained 62% of the variance in consonant-nucleus-consonant word scores at 3 months. BF-ECochG-TR as a standalone predictor tended to overestimate performance for subjects with larger negative total mismatches and underestimated the performance for those with larger positive total mismatches. Neither cochlear diameter, number of cochlear turns, nor apical insertion angle accounted for the variability in total mismatch. Comparison of ECochG-BF derived tonotopic electrode maps to the frequency allocation tables reveals substantial mismatch, explaining 26.0% of the variability in CI performance in quiet. Closer examination of the mismatch shows that basally shifted maps at high frequencies demonstrate superior performance at 3 months compared with those with apically shifted maps (toward Greenwood and Stakhovskaya et al.). The implications of these results suggest that electrophysiological-based frequency reallocation might lead to enhanced speech-perception performance, especially when compared with conventional manufacturer maps or anatomic-based mapping strategies. Future research, exploring the prospective use of ECochG-based mapping techniques for frequency allocation is underway.